Kajian Digitalisasi IKM dan UMKM Kota Surakarta - Gunawan Adi Pratio; Margono Margono; Dwi Zulkarnaen; Indra Kertati (Badan Riset dan Inovasi Daerah Kota Surakarta, 2023)
Indonesia is experiencing fluctuating economic growth and tends to decline from 2011 to 2021 and economic growth will pick up again in 2022. In 2020 the Indonesian economy, including Surakarta City, experienced a sharp decline triggered by the Coronavirus Disease (Covid-19) pandemic. Covid-19 has a high risk of increasing the number of deaths, disruption of the infrastructure repair process and large economic losses. In 2022, the Indonesian economy (5.30%), including the City of Surakarta (6.25%) will recover and improve. This year, many business units were able to adapt to changes in their external environment by carrying out various business innovations, including the application of digital technology in their business operations. Small and medium industries (IKM) and micro, small and medium enterprises (MSMEs) are one of the main drivers of the economy, where when they are willing and able to adapt to various changes, such as climate change, industrial revolution 4.0, the Covid-19 pandemic and so on, then business continuity can be maintained and even experience better development.